Estudo numérico e experimental de parâmetros de vibração em lajes de concreto - Lago, Fernanda Scussiato (2019)
Investigating the dynamic characteristics of slabs has become very important since modern structures, due to the evolution of the mechanical strength of steel and concrete, have been built lighter with longer open spans, and consequently more susceptible to the phenomena of vibration. Therefore, knowing some parameters of vibration, such as natural frequencies and damping, in the design phase, can avoid vibrations problems in the future. This research aims to study the dynamic behavior of two types concrete slabs: waffle slabs and precast ribbed slabs. Initially, experimental tests were performed using the heel impact method using accelerometer and cell phone to obtain the fundamental frequencies and damping coefficients through two methods explained in the literature review. The acceleration responses are passed in a low-pass filter to evaluate the advantages of using filters in obtaining frequencies and damping. In addition, the modal parameters of natural frequency and vibration modes are computed using analytical formulas and computer modeling by finite element software. Experimental results show that the use of cell phones is a simple and economical alternative to obtain frequency and damping parameters in slabs. The damping factors can be predicted through the two methods presented, however the logarithmic decrement method is the best alternative when using non-instrumented tests, and the frequency filters were indispensable for the evaluation of the damping of the structures. Regarding the analytical results, analytical formulations for orthotropic plates have conservative values with good prediction to the natural frequencies, although the assumption of isotropic plates can be used for an initial estimation of this parameter. The computer modeling using shell elements to represent the slab geometry has shown approximate results to the experimental values, mainly for the waffle slabs. In general, it is possible to affirm that the fundamental frequencies two-way waffle slabs have substantial relation with the shorter span, and a simplified equation for estimating this parameter can be defined.